Adjiusting determinants of addictiveness among prisoners - Dronov, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
he article deals with the dynamics of psychological patterns of drug users in the conditions of stay penalty. The author conducted addyktsiyi determine how needs or means of survival in difficult life circumstances.